A Study on the Mitigation of Global Supply Chain Disruptions - Ghafli, Mohammad; Hussaien, Qassim Aba; Shaer, Ahmad (International Journal of Supply Chain Management, 2025)
Global supply chain disruptions pose significant challenges by unexpectedly interrupting the flow of materials and products across industries. Such disruptions; whether caused by natural disasters, geopolitical events, pandemics, or other shocks (may lead to substantial financial losses and operational instability). This paper examines key strategies for mitigating these risks in a neutral, cross-industry context. We explore how inventory optimization, refurbishment, circular economy principles, and sourcing diversification contribute to supply chain resilience. Research indicates that building redundancy (e.g., safety stocks, dual sourcing) and flexibility (e.g., alternate suppliers, adaptable production) can enhance continuity in the face of disruptions [1-3). Circular economy approaches such as remanufacturing, reuse of surplus materials, and extending material shelf-life emerge as complementary strategies that reduce dependence on newly sourced supplies [4,5]. Our findings synthesize examples from multiple sectors energy, manufacturing, healthcare, and logistics— to illustrate practical applications of these strategies and their effectiveness in improving resilience. The discussion addresses implementation challenges such as cost trade-offs, regulatory considerations, and stakeholder buy-in. The paper's contribution is a unified fourpillar conceptual model: redundancy, flexibility, circularity, and technological enablers; integrated from recent literature and translated into an actionable framework for practice.